Making sense of the constellations of (im) mobility of Bangladeshi migrants in Greece - Fratsea, Loukia - Maria; Papadopoulos, Apostolos G. (Migration Letters, 2021)
Over the last three decades of the 20th century, Greece was transformed from an emigration into an immigration country and, more recently, into a country combining emigration and immigration. Initially, immigration from the ‘Balkans’ was at the heart of the country’s migration debates. However, since the early 2000s, migration inflows have been highly differentiated, and the numbers have increased for both Asian and African migrants. During the era of austerity, Bangladeshis have followed diverse employment pathways and spatial trajectories. Their so-called ‘constellations of (im)mobility’ cover an array of socio-spatial mobility patterns, ranging from being entrapped in precarious jobs to gaining access to/ striving towards more prestigious occupational positions (self-employed occupations). Drawing on recent empirical research, this paper seeks to explore the multidimensional precarity of Bangladeshi migrants living in Greek urban and rural areas. Given the dynamic interplay between macro- and micro-level processes, it also discusses aspects of agency along with practices and strategies for improving the well-being of Bangladeshi migrants in the host society.